Automating the Process of an Oil and Gas Company Property Management: Regulatory and Economic Aspects - Grigorievna Bondarenko, Tatiana; Yuryevich Annenkov, Aleksey; Arbievich Khalidov, Ibragim; Uvaysovich Soltakhanov, Anzor (International Journal of Engineering and Technology, 2018)
In this article, the authors consider the modern principles and features of maintaining the oil and gas company equipment database in the ERP system for the growth of the efficient use of property assets in oil and gas companies with a view to establishing common methodological principles and approaches thereto, and the formation of management reporting in these companies and their subsidiaries. The proposed methodology establishes the unified requirements to the management accounting and the formation of a system of effective use of assets of an oil and gas company in modern conditions, allowing to modernize and repair each technological process of the oil and gas companies both in a staged manner and, in general, and to timely receive management information for each technological process or for each business unit regarding the use of property assets of an oil and gas company. The article describes the prototype model for the classification and grouping of the company property, which can be implemented in modules on SAP or Oracle platforms in order to visualize methodology of the future system implemented on directories of a unified budget classifier. It was argued that the primary goal of the ERP system implementation was the creation of an understandable and functional system of the company asset management that would allow a much more efficient budget planning to optimize stock balances, costs for repairs, investment costs, in other words, would improve the efficiency and transparency of the entire workflow. Â Â Â